Suspensión del gobierno del Choco por contratación indevida covid 19 (2020)
Exotic "contract for quarantined markets cost the governor of Chocó the position, as confirmed this Friday by the attorney general, Fernando Carrillo, who at a press conference said that the departmental president was suspended for 3 months. Carrillo announced that the measure discipline against Governor Ariel Palacios Calderon has to do with alleged irregularities in the hiring, intended for the acquisition of products and food for low-income families facing the crisis due to the pandemic. "In the case of the Governor of Chocó it is a contract inexplicable, exotic, in relation to a foundation that, surely, does not have the competence to do so, Carrillo announced that this decision "was taken a few minutes ago", and that is why it was asked to open an investigation against those involved and suspend In addition, he said that what motivated the sanction against Palacios Calderon was the "possibility of repetition of the offense." Key words: covid 19, suspension, Governor, standards, findings.